Dietary intake of tomato and lycopene, blood levels of lycopene, and risk of total and specific cancers in adults: a systematic review and dose–response meta-analysis of prospective cohort studies - Balali, Arghavan; Fathzadeh, Kimia; Askari, Gholamreza; Sadeghi, Omid (Frontiers in Nutrition, 2025)
BackgroundThe association between tomato/lycopene intake and blood levels of lycopene with the risk of specific cancers were assessed in previous meta-analyses; however, no study evaluated the risk of overall cancer incidence/mortality. Therefore, the present systematic review and dose–response meta-analysis aimed to summarize available findings from prospective studies to examine the association between tomato/lycopene intake and lycopene levels with the risk of total and specific cancers and cancer-related mortality.MethodsA comprehensive literature search was done using Scopus, PubMed, ISI Web of Science, and Google Scholar until July 2023.ResultsIn total, 121 prospective studies were included in the systematic review and 119 in the meta-analysis. During the follow-up period of 2–32 years, a total of 108,574 cancer cases and 10,375 deaths occurred. High intakes and high levels of lycopene compared to low amounts were, respectively, associated with 5% (Pooled RR: 0.95, 95% CI: 0.92–0.98, I2 = 26.4%, p = 0.002) and 11% (Pooled RR: 0.89, 95% CI: 0.84–0.95, I2 = 15.0%, p < 0.001) reduction in overall cancer risk. Also, each 10 μg/dL increase in blood levels of lycopene was associated with a 5% lower risk of overall cancer. Moreover, we found a linear inverse association between dietary lycopene intake and prostate cancer risk (Pooled RR 0.99, 95% CI 0.97–1.00, I2 = 0, p = 0.045). Regarding cancer mortality, negative relationships were found with total tomato intake (Pooled RR: 0.89, 95% CI: 0.85–0.93, I2 = 65.7%, p < 0.001), lycopene intake (Pooled RR: 0.84, 95% CI: 0.81–0.86, I2 = 86.5%, p < 0.001) and lycopene levels (Pooled RR 0.76, 95% CI: 0.60–0.98, I2 = 70.9%, p = 0.031). Also, an inverse association was observed between blood lycopene levels and lung cancer mortality (Pooled RR: 0.65, 95% CI: 0.45–0.94, I2 = 0, p = 0.022).ConclusionOur findings show that dietary intake and blood levels of lycopene are associated with a lower risk of cancer and death due to cancer.Clinical trial registrationCRD42023432400.